2010
DOI: 10.1094/fg-2010-0923-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Frequency and Stubble Height Affect Herbage Accumulation, Nutritive Value, and Persistence of ‘Mulato II’ Brachiariagrass

Abstract: ‘Mulato II’ (Brachiaria sp.) is a warm‐season forage hybrid with superior nutritive value introduced in Florida in 2003. The objective of this study was to evaluate the effects of harvest frequencies and stubble heights on herbage accumulation (HA), nutritive value, and persistence of Mulato II brachiariagrass. The research was conducted in Ona, FL (27°N) from August to October 2007 and 2008. Treatments were the factorial combination of 2‐ and 4‐week harvest frequencies and 1‐, 3‐, and 5‐inch stubble heights w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 9 publications
5
27
0
3
Order By: Relevance
“…Herbage accumulation increased linearly (P < 0.01) from 7040 to 8120 kg ha −1 yr −1 with increasing K fertilization (Fig. Similarly, Inyang et al (2010a) found a quadratic increase in HA of the tropical grass species 'Mulato II' brachiariagrass (Brachiaria spp.) Herbage accumulation control, and the authors concluded that continual removal of forage mass without adequate K fertilization management has long-term negative effects on forage production.…”
Section: Herbage Accumulationmentioning
confidence: 67%
See 1 more Smart Citation
“…Herbage accumulation increased linearly (P < 0.01) from 7040 to 8120 kg ha −1 yr −1 with increasing K fertilization (Fig. Similarly, Inyang et al (2010a) found a quadratic increase in HA of the tropical grass species 'Mulato II' brachiariagrass (Brachiaria spp.) Herbage accumulation control, and the authors concluded that continual removal of forage mass without adequate K fertilization management has long-term negative effects on forage production.…”
Section: Herbage Accumulationmentioning
confidence: 67%
“…Although short stubble height (SH) often maximizes harvested herbage (Inyang et al, 2010a;Liu et al, 2011), repeated removal of biomass at low cutting heights may reduce plant stand and increase weed encroachment (Mislevy and Everett, 1981). Although short stubble height (SH) often maximizes harvested herbage (Inyang et al, 2010a;Liu et al, 2011), repeated removal of biomass at low cutting heights may reduce plant stand and increase weed encroachment (Mislevy and Everett, 1981).…”
mentioning
confidence: 99%
“…They observed that there was a linear decrease in HM and average daily gain (ADG) with increasing stocking rates. Inyang et al (2010b) observed that ground cover of Mulato II plots declined from 87 to 74% as the harvest stubble height decreased from 12.5 to 2.5 cm. Inyang et al (2010a) reported a linear decrease in HM and a quadratic increase in herbage accumulation rate (HAR) on bahiagrass (Paspalum notatum Flügge) and Mulato II (Brachiaria spp.)…”
mentioning
confidence: 95%
“…Under continuous stocking, maintaining an optimal canopy height has been reported to improve pasture production and persistence, as well as animal productivity. Carloto et al (2011) (INYANG et al, 2010b). Ground cover of Mulato II brachiariagrass decreased linearly from 89 to 78% as clipping stubble height decreased from 12.7 to 2.5 cm (INYANG et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%